Learning From Cancer: Extending Cell Viability by Telomerase Modulation - Sola-Ojo, Modade (My University, 2025)
Normal cells age because their telomeres shorten with every division, eventually reaching a point known as the Hayflick limit. Cancer cells avoid this fate by keeping telomerase active, giving them the ability to divide indefinitely. This commentary asks whether the same principle, if tightly controlled, could be turned toward useful ends. Control of telomerase in normal cells might promote their longevity in bioprocesses where culture stability is paramount, or in regenerative medicine, where tissues need more time to regenerate. The idea is simple, but the path forward requires serious effort to ensure safety and long-term control. In essence, understanding cancer to apply its strategic hallmarks in ways that benefit human health and technology.
Keywords: Cellular Longevity; Cancer Biology; Bioprocessing; Regenerative Medicine; Telomerase